1979
DOI: 10.1136/bmj.1.6166.777
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic antigen in breast-cancer tissue: a useful prognostic indicator.

Abstract: Summary and conclusionsSections of breast carcinomas removed from 69 patients six to 13 years previously were examined using an immunoperoxidase technique to determine whether carcinoembryonic antigen (CEA) was present. Patients who had CEA-negative tumours had significantly higher five-and 10-year survival rates. The difference was not related to the stage of the disease, postoperative treatment, or histological type of tumour.These results suggest that immunohistological assessment of CEA in breast-cancer ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(24 citation statements)
references
References 6 publications
3
21
0
Order By: Relevance
“…The positivity for CEA (38%) is comparable with the results of previous studies (Shousha et al, 1979;Walker, 1980), but staining for CEA was not predictive of response to endocrine therapy. We are continuing clinical follow-up to determine whether positive staining will predict time to recurrence of primary tumours or length of survival.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The positivity for CEA (38%) is comparable with the results of previous studies (Shousha et al, 1979;Walker, 1980), but staining for CEA was not predictive of response to endocrine therapy. We are continuing clinical follow-up to determine whether positive staining will predict time to recurrence of primary tumours or length of survival.…”
Section: Resultssupporting
confidence: 80%
“…It has been stated that the presence of carcinoembryonic antigen (CEA) (Shousha et al, 1979;Walker, 1980), and the intensity of staining for a material similar to the large glycoprotein, termed epithelial membrane antigen (EMA) (Heyderman et al, 1985), using monoclonal antibodies HMFG1 (Wilkinson et al, 1984) and NCRC-I1 (Ellis et al, 1987), is predictive of outcome. Markers such as EMA and cytokeratin (antibody CAM 5.2;Makin et al, 1984) are of possible value for the distinction of breast epithelial cells from stroma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For in stance, Shousha et al [9] found that CEA negativity was associated with a lower fre quency of nodal métastasés and significantly higher survival rates (5-10 years). Similarly, Kuhadja et al [10] found that ductal carci nomas, 3 cm or less in diameter, exhibited a significant relationship between high CEA positivity and the presence of synchronous axillary nodal métastasés.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative method of CEA detection, which is not subject to these variables, is by immunohistochemistry which permits precise localization of CEA within individual tumour cells. Although the disease cannot be monitored by this method, attempts have been made to correlate immunohistochemically demonstrable CEA with various prognostic parameters (Shousha & Lyssiotis, 1978;Shousha et al, 1979;Walker, 1980). However, conflicting results have been obtained, probably attributable to differences in the characteristics of the CEA antiserum used in the immunohistochemical method (Walker, 1980).…”
mentioning
confidence: 99%